Evolution of Anisotropy in Granular Materials: Effect of Particle Rolling and Particle Crushing - Zhou, L.L.; Chu, X.H.; Xu, Y.J. (Проблемы прочности, 2014)
The effect of particle rolling and crushing on the evolutions of the two types of anisotropy, i.e., anisotropy of particle packing (microstructure) and anisotropy of force chains, is investigated numerically using the discrete element method. To this end, the classical fabric tensor is adopted to describe the anisotropy of microstructure, while two similar orientation tensors defined by the directions of contact forces are used to characterize the anisotropy of force chains. Numerical results show that the evolutions of anisotropy follows the same tendency as the stress–strain curve, and the anisotropy of force chains is more intense than that of the microstructure. In addition, particle rolling exerts different effect on anisotropy before and after the peak stress state, and particle crushing decreases the anisotropy of granular materials.